2014
DOI: 10.1088/0964-1726/23/2/025038
|View full text |Cite
|
Sign up to set email alerts
|

Infrared light actuated shape memory effects in crystalline polyurethane/graphene chemical hybrids

Abstract: A series of crystalline shape memory polyurethanes (SMPUs) were synthesized from polycaprolactone diols and 4,4 -methylenedicyclohexyl diisocyanate (H 12 MDI) with chemical incorporation of allyl isocyanate modified graphene oxide (iGO) into the PU. Actuation of hybrid SMPUs by infrared (IR) absorption of iGO as well as the direct heat actuated SMPUs has been studied in terms of the isothermal crystallization rate, near-IR absorption, and thermal, mechanical, and shape memory properties. It was found that iGO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Thakur et al (2013) have demonstrated that castor oil-modified hyperbranched PU and graphene-oxide (without functionalization) can result in a shape recovery of ~99.5% with shape fixity of ~90%. Park et al (2014) have demonstrated that PU and allyl isocyanate modified graphene oxide can also be actuated by infrared absorption, with a resulting shape recovery of 90%.…”
Section: Graphene In Shape Memory Materialsmentioning
confidence: 99%
“…Thakur et al (2013) have demonstrated that castor oil-modified hyperbranched PU and graphene-oxide (without functionalization) can result in a shape recovery of ~99.5% with shape fixity of ~90%. Park et al (2014) have demonstrated that PU and allyl isocyanate modified graphene oxide can also be actuated by infrared absorption, with a resulting shape recovery of 90%.…”
Section: Graphene In Shape Memory Materialsmentioning
confidence: 99%
“…Heating can be applied directly or non-directly. Stimuli such as electrical resistive heating [14], magnetic field [15], infrared and UV heating light [16,17] are examples of non-direct heating. Although there are various actuation methods for activating SMPs, but most of shape memory polymers are only able to be actuated through direct heating [18] and triggering with other stimulus is more complex.…”
Section: Introductionmentioning
confidence: 99%
“…These unique properties of graphene have been used to produce different multi-stimuli responsive SMPs. Infrared light actuated SMPs are a class of these materials and some studies have been done in this regard [17,37,38]. Kashif et al [37] have produced shape memory polyolefin elastomer/modified graphene nanocomposites responding to infrared light with healing properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modification of PU with graphene is a way of developing a new generation of materials for a wider spectrum of industrial applications. PU/graphene nanocomposites may display significant improvements in mechanical and thermal properties [29,30], the shape-memory effect [31,32], electromagnetic shielding capabilities [33], and conductivity [34]. Table 1.…”
Section: Introductionmentioning
confidence: 99%